2004
DOI: 10.1016/j.adnc.2004.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Attachment and Other Correlates of Postnatal Maternal Attachment to Twins

Abstract: Although the study findings support a modest relationship between prenatal and postnatal attachment in mothers of twins, maternal depression was also significant in explaining postnatal attachment. Postpartum depression, having a cesarean delivery, and the experience of a NICU admission for 1 or both twins further influenced the relationship between prenatal attachment and postnatal attachment. When fostering attachment in mothers of twins, nurses should assess for symptoms of depression and pay particular att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 60 publications
6
69
0
6
Order By: Relevance
“…Müller [102] and Damato [103], using questionnaires, found a significant correlation between prepartum and postpartum attachment scores. The same was found by Siddiqui and Hägglöf [104] who assessed postpartum attachment from videotaped face-to-face interaction.…”
Section: Causesmentioning
confidence: 99%
“…Müller [102] and Damato [103], using questionnaires, found a significant correlation between prepartum and postpartum attachment scores. The same was found by Siddiqui and Hägglöf [104] who assessed postpartum attachment from videotaped face-to-face interaction.…”
Section: Causesmentioning
confidence: 99%
“…Este resultado también compartido por Damato (34) , Dudek, (p 0'001) (35) y Muller-Mix (36) , ya que, la separación que se produce con el ingreso del RN en la UCIN, unido al uso de técnicas y procedimientos invasivos, provoca la creación de un terreno hostil que dificulta la interacción entre la madre y el RN.…”
Section: Discusión Y Limitaciones Discusiónunclassified
“…En relación a otra variable obstétrica, el tipo de parto, no se ha identificado relación con el apego. Sin embargo otros autores señalan la cesárea programada con menores puntuaciones de apego (34,37) , debido, en parte, a la interrupción del proceso natural del parto.…”
Section: Discusión Y Limitaciones Discusiónunclassified
“…Higher scores indicate greater attachment of mother to the fetus. 26 This inventory demonstrated higher levels of internal consistency in the two reviewed studies (α=0.89) 15,16 when compared to the original version (α=0.81), 26 demonstrating that the tool is reliable. Regarding the construct validity, the FA showed that one factor accounted for 79.0% of total variance.…”
mentioning
confidence: 99%
“…48 The internal consistency of the original version (α=0.85 -4-week babies, α=0.76 -4-month babies, and α=0.85 -8-month babies) 47 showed lower values than those found in two other studies, with α>0.90. 13,16 Thus, the MAI is a robust tool to measure the attachment between mother and baby.…”
mentioning
confidence: 99%